Análise da competitividade da cadeia de produção do feijão-comum: um estudo de caso utilizando a matriz de análise de política (MAP) - Assunção, Paulo Eterno Venâncio (2013)
The common bean is an important component of the diet of the Brazilian people, the main source of vegetable protein consumed by the population. The bean has its own characteristics regarding its production process, which differs from other grains, it is produced in three seasons, which occur in different ways and at different times of the year. Public policies adopted within rural aimed try to develop the productive chain, trying to make it more competitive and more able to compete with other chains. In that sense, the Policy Analysis Matrix (PAM) is an important tool for evaluation of these policies and how these policies can provide the setting conducive to the development chain. The general objective of this research was to analyze the competitiveness of bean production in Goiás using the Policy Analysis Matrix. Data were collected on a property representative in the municipality of Cristalina municipality with higher production within the state, and an agribusiness representative. Sought with these data raise the main costs of the production chain of beans. The results obtained for the three harvests, infer that the productive chain of beans in the first and second crop meets with great difficulties of survival, not being competitive at the international level. The first and second crop have high rates of unprotected, indicating that require investments in the same order so that they can survive profitably. The third season introduces a scenario a little more conducive, but actions need to be taken so that this crop can become more competitive. For culture under study is not competitive enough to have the latest technology, but also public actions that benefit and provide the product competitiveness.